Industrial dust removal filter bag capable of preventing oil stain pollution and preparation method of industrial dust removal filter bag
The polyester filter cloth is sorted through neutral protease treatment and multi-function finishing agent to form a hydrophobic surface, combined with nano zinc oxide to improve the pollution resistance, solve the problem of water and oil repellent in harsh environments of industrial dust removal filter bags, and improve the filter bags Durability and dust removal efficiency.
Patent Information
- Application Number
- CN202411654873.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing industrial dust removal filter bags have poor water and oil repellent performance under high temperature, high humidity, strong acid and alkali or oil-gas pollution environments, resulting in moisture and oil adhesion, resulting in paste and blockage of bags, affecting dust removal efficiency and service life.
The polyester filter cloth is treated with neutral protease, combined with multifunctional finishing agent and nano zinc oxide, and is sorted through a two-thick and two-rolling process to form a hydrophobic surface with a micron-scale structure, imitating the surface structure of the lotus leaf, enhancing the anti-fouling and self-cleaning properties. And the stability and durability of the polymer are improved by semi-continuous emulsion polymerization.
It significantly improves the anti-fouling and self-cleaning ability of polyester filter cloth, enhances the anti-oil and dirty performance, extends the service life of the filter bag, and maintains good waterproof, oil-proof and anti-fouling function in wet and dry states.
Smart Images

Figure BDA0005141883030000161
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of dust removal filter bag processing, and in particular to an industrial dust removal filter bag resistant to oil stain pollution and a preparation method thereof. Background Art
[0002] In the industrial flue gas purification process such as coal-fired boilers, waste incineration, steel smelting, calcium carbide chemical industry, etc., bag dust removal filter materials play a vital role. However, the filter bag materials in the existing technology still face some challenges, especially in harsh working environments with high temperature, high humidity, strong acid and alkali or oil and gas pollution. The filter bags often show poor water and oil repellency. This situation makes it easy for water and oil to adhere to the surface of the filter bags, which in turn causes bag sticking and bag blockage, affecting the normal operation of the filter bags and shortening their service life.
[0003] During the long-term use of industrial dust filter bags in the prior art, while filtering dust and flue gas, the oily substances in the dust and flue gas are easily attached to the filter bags, causing blockage of the filter bags and reducing the dust removal efficiency. After the filter cloth is contaminated, the cleaning liquid cannot wet the filter cloth well, making the stains difficult to remove. Therefore, in order to meet these challenges, new filter bag materials need to continue to be improved in terms of water repellency, oil repellency, high temperature resistance, corrosion resistance, oxidation resistance, etc., to improve their durability and service life, ensure the dust removal effect of the filter bag and the long-term stable operation of the equipment, and further improve the anti-oil performance of the filter bag.
[0004] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0005] The object of the present invention is to provide an industrial dust removal filter bag resistant to oil stain pollution and a preparation method thereof, so as to solve the technical problems in the prior art that the stains on the filter bag are difficult to remove and the oil stain resistance performance needs to be improved.
[0006] The purpose of the present invention can be achieved by the following technical solution: A method for preparing an industrial dust filter bag that is resistant to oil stain pollution comprises the following steps:
[0007] S1, adding hydrogen peroxide, penetrant JFC, sodium pyrophosphate and polyester filter cloth into a reactor and stirring, the reactor temperature is 50-60°C, and the reaction is kept warm for 50-60 minutes to obtain a pretreated polyester filter cloth;
[0008] S2, adding the pretreated polyester filter cloth and neutral protease into the reactor and stirring, adding sodium hydroxide solution to adjust the pH of the system to 7-8, setting the reactor temperature to 30-40°C, keeping the temperature for reaction for 30-50 minutes, and post-processing to obtain the stripped filter cloth;
[0009] S3, using a multifunctional finishing agent to perform a two-immersion and two-rolling process on the stripped filter cloth to obtain a dust-removing, water-repellent and oil-repellent filter cloth;
[0010] S4, cutting and sewing the dust-removing, water-repellent and oil-repellent filter cloth to obtain a dust-removing, water-repellent and oil-repellent filter bag.
[0011] Furthermore, the hydrogen peroxide, the penetrant JFC, and the sodium pyrophosphate are used in a ratio of 3000 mL:100 g:300 g, and the bath ratio is 1 g:20 mL.
[0012] Furthermore, the neutral protease concentration is 5%, the ratio of pre-treated polyester filter cloth and neutral protease usage is 1g:20mL, and the concentration of sodium hydroxide solution is 1%; post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, suction filtration is performed, the filter cake is washed to neutrality and then dried, the filter cake is placed in a drying oven at a temperature of 80-90°C, and dried to constant weight to obtain a stripped filter cloth.
[0013] The reaction mechanism of neutral protease is:
[0014] The outer layer of the fiber scales of the polyester filter cloth has a high cross-linking density of disulfide bonds, making it difficult for proteases to diffuse into it. Therefore, when the polyester filter cloth is first treated with an oxidant, the oxidant can effectively cut the cystine disulfide bonds, increase the accessibility of the protease, and make it easier for the protease to penetrate into the fiber and exert its effect, especially in the outer layer of the scales, thereby promoting the hydrolysis. Treating the polyester filter cloth with a protease can promote changes in its surface structure, thereby improving its performance. When the protease acts on the polyester fiber, it mainly acts by hydrolyzing the adhesive in the cell membrane complex, gradually expanding to the inside of the fiber to perform surface stripping treatment on the fiber, and forming a rough surface with a micron-level structure on the surface of the polyester filter cloth. This structure imitates the microstructure of the lotus leaf surface and can achieve hydrophobic properties similar to those of the lotus leaf. The micron structure of the lotus leaf surface mainly includes micron-level papillae and nanometer-level bumps. These structures enable water droplets to form rolling water beads on the surface instead of infiltrating the surface, thereby exhibiting the characteristics of being water-resistant and self-cleaning.
[0015] Furthermore, the multifunctional finishing agent is obtained by processing the following steps:
[0016] A1. Add the mixture of compound emulsifier, basic monomer, fluorine-containing monomer, hydrophilic monomer, initiator, crosslinking agent and deionized water into a high shear dispersing emulsifier for dispersion and stirring for 10-20 min and emulsification time for 30-40 min to obtain a pre-emulsion;
[0017] A2. Add pre-emulsion, compound emulsifier, dispersed zinc oxide powder, initiator and deionized water into the reactor and stir. The temperature of the reactor is raised to 70-80°C, the reaction time is 10-20min, the speed of the reactor is 1000-2000r / min, ammonia water is added to adjust the pH of the system to 6-7, the temperature of the reactor is raised to 85-90°C, the insulation time is 2-3h, the speed of the reactor is 2000-3000r / min, and the multifunctional finishing agent is post-treated.
[0018] Furthermore, the dosage ratio of the compound emulsifier, the basic monomer, the fluorine-containing monomer, the hydrophilic monomer, the initiator, the crosslinking agent and the deionized water is 2-4:4-6:50-60:2-4:1-2:1-2:500-800, the compound emulsifier is composed of sodium dodecylbenzene sulfonate and alcohol polyoxyethylene ether in a weight ratio of 1:2, the basic monomer is a mixture of methyl methacrylate, butyl acrylate and isooctyl acrylate, the fluorine-containing monomer is dodecafluoroheptyl methacrylate, the hydrophilic monomer is allyl polyoxyethylene ether, the initiator is ammonium persulfate, and the crosslinking agent is N-hydroxymethyl acrylamide; the speed of the high shear dispersing emulsifier is 5000-6000r / min; in step A2, the dosage ratio of the pre-emulsion, the compound emulsifier, the dispersed zinc oxide powder, the initiator and the deionized water is 10-20:10-20:3-6:50-60:200-300.
[0019] The reaction mechanism of the multifunctional finishing agent is:
[0020] The fluorine-containing monomer is dodecafluoroheptyl methacrylate, which can give the finishing agent excellent film-forming properties and adhesion, thereby improving the intramolecular stability; the cross-linking monomer N-hydroxymethyl acrylamide can undergo self-crosslinking or cross-linking reactions with the fibers to form a strong and tough film on the surface of the filter cloth, thereby improving the durability of the finished filter cloth. The polar groups it carries can promote the polymerization reaction to form a network structure, thereby improving the covalent bonding between the polymer and the fiber, thereby improving the wash resistance; the hydrophilic monomer allyl polyoxyethylene ether contains hydrophilic polyoxyethylene ether segments, and the polymer containing the polyoxyethylene ether segments will react with water in water and arrange on the surface of the polymer, thereby giving the surface hydrophilicity and giving the finishing agent easy decontamination properties.
[0021] Furthermore, the dispersed zinc oxide powder is obtained by processing the following steps:
[0022] B1. Add nano zinc oxide powder, titanate coupling agent and deionized water into an electromagnetic stirrer, raise the temperature of the stirrer to 90-100, keep stirring for 1 hour, and post-treat to obtain modified zinc oxide;
[0023] B2. Add modified zinc oxide, dispersant and deionized water into an ultrasonic disperser, perform ultrasonic dispersion for 30-40 minutes, and perform post-treatment to obtain dispersed zinc oxide powder.
[0024] Furthermore, the dosage ratio of the nano zinc oxide powder, titanate coupling agent, and deionized water is: 1-2g: 5-8g: 100-160mL, and the speed of the electromagnetic stirrer is 2000-3000r / min; the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, suction filtration is performed, the filter cake is washed to neutrality and then dried, the filter cake is placed in a drying oven at a temperature of 80-90°C, and dried to constant weight to obtain modified zinc oxide; in step B2, the dosage ratio of the modified zinc oxide, oligomeric sodium acrylate, and deionized water is: 1-2g: 0.5-2.5g: 100-150mL, and the shear speed of the ultrasonic disperser is 4000-5000r / min; the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, suction filtration is performed, the filter cake is washed to neutrality and then dried, the filter cake is placed in a drying oven at a temperature of 80-90°C, and dried to constant weight to obtain dispersed zinc oxide powder.
[0025] The reaction mechanism of dispersing zinc oxide powder is:
[0026] The adsorbed water on the surface of nano ZnO is easily coupled with the -OR functional group of the coupling agent to form a strong hydrogen bond, forming a tight organic monolayer on the surface of nano ZnO, which can play a steric hindrance effect and modify the surface of nano ZnO. The hydroxyl reaction group of the titanate coupling agent can improve the compatibility between nano particles and organic materials, and easily form a covalent chemical bond between the surface fibers of the filter cloth and the nano particles, so that the surface of the powder particles is effectively coated, thereby making the surface of the filler organic and changing the surface properties of the filler. Therefore, the hydrolytic stability of the filling system can be improved, the compatibility with the polymer can be increased, the viscosity can be reduced, and the dispersion stability of the powder in the dispersion can be improved.
[0027] Furthermore, the dust-removing, water-repellent and oil-repellent filter cloth is processed by the following steps:
[0028] C1. Soak the stripped filter cloth in a padding machine tank, with a multifunctional finishing dosage of 60-80% and a soaking time of 10-20 minutes, and squeeze it through a two-roller mill with a rolling pressure of 400KN-600KN, a rolling speed of 100-150m / min, and a winding speed of 100-280m / min. Put it in a heat setting machine for pre-baking, with a pre-baking temperature of 90-110°C, a pre-baking time of 5-10min, a baking temperature of 140-160°C, and a baking time of 5-10min to obtain a pre-impregnated filter cloth;
[0029] C2. Soak the pre-impregnated filter cloth in an impregnation machine tank with a multifunctional finishing dosage of 60-80% and an immersion time of 20-40 min. Squeeze the pre-impregnated filter cloth through a two-roller mill with a rolling pressure of 600 KN-800 KN, a rolling speed of 150-200 m / min, and a winding speed of 200-380 m / min. Pre-bake the pre-impregnated filter cloth in a heat setting machine at a pre-bake temperature of 90-110° C. for 5-10 min and a baking temperature of 170-190° C. for 5-10 min to obtain a dust-removing, water-repellent, and oil-repellent filter cloth.
[0030] The present invention has the following beneficial effects:
[0031] 1. The present invention uses neutral protease to treat polyester filter cloth, which can promote the change of its surface structure and thus improve its performance. When the protease acts on the polyester fiber, it mainly hydrolyzes the adhesive in the cell membrane complex and gradually expands to the inside of the fiber to perform surface stripping treatment on the fiber, forming a rough surface with a micron-level structure on the surface of the polyester filter cloth. This structure imitates the microstructure of the lotus leaf surface and can achieve hydrophobic properties similar to those of the lotus leaf. The micron structure of the lotus leaf surface mainly includes micron-level papillae and nano-level bumps. These structures enable water droplets to form rolling water beads on the surface instead of infiltrating the surface, thereby exhibiting water-free and self-cleaning characteristics. This surface treatment method can effectively improve the performance of the polyester filter cloth and enhance its anti-fouling and self-cleaning capabilities.
[0032] 2. The present invention improves the compatibility between nano zinc oxide particles and organic materials, increases the compatibility with polymers, reduces viscosity, and improves the dispersion stability of powders in dispersions by adding nano zinc oxide and hydroxyl reaction groups of titanate coupling agents to fluorine-containing polymers; the introduced hydrophilic monomer allyl polyoxyethylene ether, based on the bidirectional effect of fluorine in the polymer structure of the multifunctional finishing agent and the hydrophilic part, can make the filter cloth have good waterproof and oil-proof properties in a dry state and excellent easy-to-clean properties in a wet state, thereby maintaining good waterproof, oil-proof and anti-fouling functions and preventing dirt from penetrating into the interior of the filter cloth; two opposing effects can be achieved at the same time, and the cross-linking monomer N-hydroxymethyl acrylamide can undergo self-crosslinking or cross-linking reaction with the fiber to form a strong and tough film on the surface of the filter cloth, thereby improving the durability of the finished filter cloth, thereby improving the long-term protective performance and easy-to-wash performance of the filter bag, thereby extending its service life.
[0033] 3. The present invention also uses a semi-continuous emulsion polymerization method to continuously add the monomers to the reaction for polymerization in multiple times. In this monomer-starved polymerization method, a certain amount of emulsifier is semi-continuously added according to a certain procedure. The polymerization reaction rate and heat release rate are controlled by controlling the speed of adding materials. The polymerization time is relatively long, so that the system is in a relatively high stable state during the entire emulsion polymerization process, and the copolymer composition of the emulsion polymer is effectively controlled, avoiding the problem of gelation caused by excessive intermittent polymerization rate, and the emulsion polymerization system has high stability. DETAILED DESCRIPTION
[0034] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] The penetrant JFC in the present invention is selected from Taizhou Jiayin Chemical Co., Ltd.;
[0036] The titanate coupling agent NTC401 in the present invention is selected from Jinan Rongzheng Chemical Co., Ltd.;
[0037] The neutral protease in the present invention is selected from Weifang Ruichen Biotechnology Co., Ltd.;
[0038] Polyester-cotton filter cloth can be divided into two categories according to its material: one is natural fiber, such as wool, silk, linen, and fiber; the other is chemical synthetic fiber, such as polyester, nylon, polypropylene, modified acrylic wax, aromatic polyamide, vinylon, nylon, polyester fiber and some new synthetic fibers that are constantly being introduced.
[0039] Example 1
[0040] This embodiment provides a method for preparing an industrial dust filter bag that is resistant to oil stain pollution, comprising the following steps:
[0041] S1. Preparation of pretreated polyester filter cloth
[0042] Weigh: 3000 mL of hydrogen peroxide, 100 g of penetrant JFC, 300 g of sodium pyrophosphate, and 100 g of polyester filter cloth, add them into a reactor and stir, the reactor temperature is 50°C, and the temperature is kept for 50 minutes to obtain a pretreated polyester filter cloth;
[0043] S2. Preparation of stripping filter cloth
[0044] Weigh: 100 g of pretreated polyester filter cloth, 2000 mL of neutral protease, add 1% sodium hydroxide solution to adjust the pH of the system to 7, the reactor temperature is 30°C, keep warm for 30 minutes, lower the reactor temperature to room temperature, filter, wash the filter cake until it is neutral and then dry it, put the filter cake in a drying oven at 80°C, dry it to constant weight, and obtain a stripped filter cloth;
[0045] S3. Preparation of pre-emulsion
[0046] Sodium dodecylbenzene sulfonate and alcohol polyoxyethylene ether are mixed uniformly in a weight ratio of 1:2 to obtain a composite emulsifier; the basic monomer is a mixture of methyl methacrylate, butyl acrylate and isooctyl acrylate in a weight ratio of 1:2:3;
[0047] Weigh: 200 g of compound emulsifier, 400 g of base monomer, 5000 g of dodecafluoroheptyl methacrylate, 200 g of allyl polyoxyethylene ether, 100 g of ammonium persulfate, 100 g of N-hydroxymethyl acrylamide, and 60000 mL of deionized water, add them into a high shear dispersing emulsifier, disperse and stir for 10 min, and emulsify for 30 min to obtain a pre-emulsion;
[0048] S4. Preparation of modified zinc oxide
[0049] Weigh: 100 g of nano zinc oxide powder, 500 g of titanate coupling agent, and 10,000 mL of deionized water, add them into an electromagnetic stirrer, raise the temperature of the stirrer to 90° C., keep warm and stir for 1 hour, after the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake until it is neutral and then dry it, put the filter cake into a drying oven at 80° C., and dry it to constant weight to obtain modified zinc oxide;
[0050] S5. Preparation of dispersed zinc oxide
[0051] Weigh: 100 g of modified zinc oxide, 50 g of oligomeric sodium acrylate, and 1000 mL of deionized water, add them into an ultrasonic disperser, and perform ultrasonic dispersion for 30 min. The shear speed of the ultrasonic disperser is 4000 r / min. After the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed to neutrality and then dried, and the filter cake is placed in a drying oven at a temperature of 80° C. and dried to constant weight to obtain dispersed zinc oxide powder;
[0052] S6. Preparation of multifunctional finishing agent
[0053] Weigh: 100g of pre-emulsion, 100g of compound emulsifier, 30g of dispersed zinc oxide powder, 500g of initiator, and 8000mL of deionized water, add them into a reactor and stir, raise the temperature of the reactor to 70°C, react for 10min, rotate the reactor at 1000r / min, add ammonia water to adjust the pH of the system to 6, raise the temperature of the reactor to 85°C, keep warm for 2h, rotate the reactor at 2000r / min, and post-treat with a multifunctional finishing agent;
[0054] S7. Preparation of pre-impregnated filter cloth
[0055] Weigh: 2kg of peeled filter cloth, soak it in a padding machine tank, with a multifunctional finishing agent dosage of 60%, and a soaking time of 10 minutes, squeeze it through a two-roller mill, with a rolling pressure of 400KN, a rolling speed of 100m / min, and a winding speed of 100m / min, and put it into a heat setting machine for pre-baking, with a pre-baking temperature of 90°C and a pre-baking time of 5 minutes, and a baking temperature of 140°C and a baking time of 5 minutes to obtain a pre-impregnated filter cloth;
[0056] S8. Preparation of water- and oil-resistant filter cloth
[0057] Weigh: 2 kg of pre-impregnated filter cloth, soak it in an impregnation mill tank, with a multifunctional finishing dosage of 60%, an immersion time of 20 min, squeeze it through a two-roll mill, with a rolling pressure of 600 KN, a rolling speed of 150 m / min, and a winding speed of 200 m / min, put it into a heat setting machine for pre-baking, with a pre-baking temperature of 90 ° C, a pre-baking time of 5 min, a baking temperature of 170 ° C, and a baking time of 5 min, to obtain a dust-removing, water-repellent and oil-repellent filter cloth.
[0058] Example 2
[0059] This embodiment provides a method for preparing an industrial dust filter bag that is resistant to oil stain pollution, comprising the following steps:
[0060] S1. Preparation of pretreated polyester filter cloth
[0061] Weigh: 3500 mL of hydrogen peroxide, 150 g of penetrant JFC, 350 g of sodium pyrophosphate, and 150 g of polyester filter cloth, add them into a reactor and stir, raise the temperature of the reactor to 55°C, and keep the temperature for 55 minutes to obtain a pretreated polyester filter cloth;
[0062] S2. Preparation of stripping filter cloth
[0063] Weigh: 150 g of pretreated polyester filter cloth, 2500 mL of neutral protease, add 1% sodium hydroxide solution to adjust the system pH to 7, the reactor temperature is 35°C, keep warm for 40 minutes, lower the reactor temperature to room temperature, filter, wash the filter cake until it is neutral and then dry it, put the filter cake in a drying oven at 85°C, dry it to constant weight, and obtain a stripped filter cloth;
[0064] S3. Preparation of pre-emulsion
[0065] Sodium dodecylbenzene sulfonate and alcohol polyoxyethylene ether are mixed evenly in a dosage ratio of 1:2 to obtain a composite emulsifier; the basic monomer is a mixture of methyl methacrylate, butyl acrylate and isooctyl acrylate in a weight ratio of 1:2:3;
[0066] Weigh: 350 g of compound emulsifier, 500 g of base monomer, 5500 g of dodecafluoroheptyl methacrylate, 300 g of allyl polyoxyethylene ether, 150 g of ammonium persulfate, 150 g of N-hydroxymethyl acrylamide, and 70000 mL of deionized water, add into a high shear dispersing emulsifier, disperse and stir, stir for 15 min, emulsify for 35 min, and obtain a pre-emulsion;
[0067] S4. Preparation of modified zinc oxide
[0068] Weigh: 150g of nano zinc oxide powder, 600g of titanate coupling agent, and 13000mL of deionized water, add them into an electromagnetic stirrer, raise the temperature of the stirrer to 95°C, and stir for 1.5h. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake until it is neutral, and then drain it. Put the filter cake in a drying oven at 85°C and dry it to constant weight to obtain modified zinc oxide;
[0069] S5. Preparation of dispersed zinc oxide
[0070] Weigh: 150 g of modified zinc oxide, 80 g of oligomeric sodium acrylate, and 1300 mL of deionized water, add them into an ultrasonic disperser, and perform ultrasonic dispersion for 35 min. The shear speed of the ultrasonic disperser is 4500 r / min. After the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed to neutrality and then dried, and the filter cake is placed in a drying oven at a temperature of 85° C. and dried to constant weight to obtain dispersed zinc oxide powder;
[0071] S6. Preparation of multifunctional finishing agent
[0072] Weigh: 150g of pre-emulsion, 150g of compound emulsifier, 50g of dispersed zinc oxide powder, 550g of initiator, and 8500mL of deionized water, add them into a reactor and stir, raise the temperature of the reactor to 75°C, react for 15min, rotate the reactor at 1500r / min, add ammonia water to adjust the pH of the system to 6, raise the temperature of the reactor to 90°C, keep warm for 2.5h, rotate the reactor at 2500r / min, and post-treat with a multifunctional finishing agent;
[0073] S7. Preparation of pre-impregnated filter cloth
[0074] Weigh: 2kg of peeled filter cloth, soak it in a padding machine tank, with a multifunctional finishing agent dosage of 70%, and a soaking time of 15 minutes, squeeze it through a two-roll mill, with a rolling pressure of 500KNKN, a rolling speed of 130m / min, and a winding speed of 200m / min, and put it into a heat setting machine for pre-baking, with a pre-baking temperature of 100°C, a pre-baking time of 8 minutes, and a baking temperature of 150°C, and a baking time of 8 minutes to obtain a pre-impregnated filter cloth;
[0075] S8. Preparation of water- and oil-resistant filter cloth
[0076] Weigh: 2 kg of pre-impregnated filter cloth, soak it in an impregnation machine tank, with a multifunctional finishing dosage of 70%, an immersion time of 30 min, squeeze it through a two-roll mill, with a rolling pressure of 700 KNKN, a rolling speed of 180 m / min, and a winding speed of 300 m / min, put it into a heat setting machine for pre-baking, the pre-baking temperature is 100 ° C, the pre-baking time is 8 min, the baking temperature is 180 ° C, and the baking time is 8 min, to obtain a dust-removing, water-repellent and oil-repellent filter cloth.
[0077] Example 3
[0078] This embodiment provides a method for preparing an industrial dust filter bag that is resistant to oil stain pollution, comprising the following steps:
[0079] S1. Preparation of pretreated polyester filter cloth
[0080] Weigh: 4000 mL of hydrogen peroxide, 200 g of penetrant JFC, 400 g of sodium pyrophosphate, and 200 g of polyester filter cloth, add them into a reactor and stir, raise the temperature of the reactor to 60°C, and keep the temperature for 60 minutes to obtain a pretreated polyester filter cloth;
[0081] S2. Preparation of stripping filter cloth
[0082] Weigh: 200 g of pretreated polyester filter cloth, 3000 mL of neutral protease, add 1% sodium hydroxide solution to adjust the system pH to 8, raise the reactor temperature to 40°C, keep warm for 50 minutes, lower the reactor temperature to room temperature, filter, wash the filter cake until it is neutral and then dry it, put the filter cake in a drying oven at 90°C, dry it to constant weight, and obtain a stripped filter cloth;
[0083] S3. Preparation of pre-emulsion
[0084] Sodium dodecylbenzene sulfonate and alcohol polyoxyethylene ether are mixed evenly in a dosage ratio of 1:2 to obtain a composite emulsifier; the basic monomer is a mixture of methyl methacrylate, butyl acrylate and isooctyl acrylate in a weight ratio of 1:2:3;
[0085] Weigh: 400 g of compound emulsifier, 600 g of base monomer, 6000 g of dodecafluoroheptyl methacrylate, 400 g of allyl polyoxyethylene ether, 200 g of ammonium persulfate, 200 g of N-hydroxymethyl acrylamide, and 80000 mL of deionized water, add them into a high shear dispersing emulsifier, disperse and stir for 20 min, and emulsify for 40 min to obtain a pre-emulsion;
[0086] S4. Preparation of modified zinc oxide
[0087] Weigh: 200g of nano zinc oxide powder, 800g of titanate coupling agent, and 16000mL of deionized water, add them into an electromagnetic stirrer, raise the temperature of the stirrer to 100°C, and stir for 2h. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake until it is neutral, and then drain it. Put the filter cake in a drying oven at 90°C and dry it to constant weight to obtain modified zinc oxide;
[0088] S5. Preparation of dispersed zinc oxide
[0089] Weigh: 200 g of modified zinc oxide, 100 g of oligomeric sodium acrylate, and 1500 mL of deionized water, add them into an ultrasonic disperser, and perform ultrasonic dispersion for 40 min. The shear speed of the ultrasonic disperser is 5000 r / min. After the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed to neutrality and then dried, and the filter cake is placed in a drying oven at a temperature of 90° C. and dried to constant weight to obtain dispersed zinc oxide powder;
[0090] S6. Preparation of multifunctional finishing agent
[0091] Weigh: 200g of pre-emulsion, 200g of compound emulsifier, 60g of dispersed zinc oxide powder, 600g of initiator, and 9000mL of deionized water, add them into a reactor and stir, raise the temperature of the reactor to 80°C, react for 20min, rotate the reactor at 2000r / min, add ammonia water to adjust the pH of the system to 7, raise the temperature of the reactor to 95°C, keep warm for 3h, rotate the reactor at 3000r / min, and post-treat with a multifunctional finishing agent;
[0092] S7. Preparation of pre-impregnated filter cloth
[0093] Weigh: 2kg of peeled filter cloth, soak it in a padding machine tank, with a multifunctional finishing dosage of 80%, and a soaking time of 20 minutes, squeeze it through a two-roller mill, with a rolling pressure of 600KN, a rolling speed of 150m / min, and a winding speed of 280m / min, and put it into a heat setting machine for pre-baking, with a pre-baking temperature of 110°C and a pre-baking time of 10 minutes, and a baking temperature of 160°C and a baking time of 10 minutes to obtain a pre-impregnated filter cloth;
[0094] S8. Preparation of water- and oil-resistant filter cloth
[0095] Weigh: 2 kg of pre-impregnated filter cloth, soak it in an impregnation machine tank, with a multifunctional finishing dosage of 80%, an immersion time of 30 minutes, squeeze it through a two-roll mill, with a rolling pressure of 800KNKN, a rolling speed of 200m / min, and a winding speed of 380m / min, put it into a heat setting machine for pre-baking, the pre-baking temperature is 110°C, the pre-baking time is 10 minutes, the baking temperature is 190°C, and the baking time is 10 minutes, to obtain a dust-removing, water-repellent and oil-repellent filter cloth.
[0096] Comparative Example 1
[0097] The difference between this comparative example and Example 3 is that in step S6, no dispersed zinc oxide is added.
[0098] Comparative Example 2
[0099] The difference between this comparative example and Example 3 is that in step S3, no hydrophilic monomer is added.
[0100] Comparative Example 3
[0101] The difference between this comparative example and Example 3 is that in step S3, no cross-linking agent is added.
[0102] Performance Testing:
[0103] The performance of industrial dust filter bags against oil stain pollution in Examples 1-3 and Comparative Examples 1-4 was tested, wherein:
[0104] The oil repellency of the sample is evaluated according to the standard AATCC118-2013 "Oil Repellency: Hydrocarbon Resistance Test". The hydrocarbon resistance test method is used to evaluate the wetting resistance of polyester filter cloth to a series of liquid hydrocarbons with different surface tensions, detect the presence of fluorine compound finishing agents or other compounds that can reduce surface tension on various polyester filter cloths, and use a series of standard test solutions composed of liquid hydrocarbons with different surface tensions to drop on the surface of the polyester filter cloth to observe the wetting, adsorption and contact angle of the sample;
[0105] According to the test method of standard AATCC193-2012 "Water Repellency: Water and Alcohol Solution Resistance Test": a series of water and isopropanol solutions with different surface tensions are selected to evaluate the moisture resistance of polyester filter cloth to determine the effect of low-energy surface protection finishing of various types of polyester filter cloth. Drop the standard test solution on the surface of the polyester filter cloth and observe the wetting, adsorption and contact angle. The water repellency level is the highest level of the test solution that does not wet the surface of the polyester filter cloth;
[0106] According to the standard GB / T30159.1-2013 "Testing and evaluating the antifouling performance of textiles Part 1: Stain resistance", the liquid stain method and solid stain are tested; the principle of the liquid stain method test is to add the specified liquid dirt to the horizontal surface of the sample, observe the wetting, wicking and contact angle of the droplets on the sample surface, and evaluate the degree of resistance of the sample to liquid dirt. The test selects first-grade pressed finished oil or soy sauce as the dirt, takes two samples, and the samples are placed flat on 2 layers of filter paper. 0.05mL of dirt is dropped on 3 parts of the sample. After 30s, each drop is observed at a 45° angle and rated;
[0107] The solid contamination method is to fix the sample in a test tube filled with specified solid dirt, turn the test tube over to make the sample fully contact with the dirt, compare the color difference between the test stained part and the unstained part with a gray card through color change, and evaluate the sample's resistance to solid dirt contamination. The test uses a mixture of dust and high-pigment carbon black as dirt. Take 2 samples, place the samples on the sample fixing sheet, wrap them in the tube body, and then place the dirt at the bottom of the tube. Put the test tube into a protective bag and put it in a tumbling box. Roll it 200 times, take out the sample, use a hair dryer to remove the surface dirt, and rate it. The specific test results are shown in Table 1:
[0108] Table 1-Performance test data of samples
[0109]
[0110] Data Analysis:
[0111] It can be seen from the relevant data in Table 1 that, compared with the comparative example, the industrial dust removal filter bag for preventing oil stain pollution provided by the present invention has waterproof and oil-proof properties in a dry state and easy decontamination properties in a wet state, thereby improving the long-term protective performance and easy washing performance of the filter bag, thereby extending its service life.
[0112] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
[0113] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0114] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing an industrial dust filter bag that is resistant to oil stain pollution, characterized in that: The following steps are involved: S1, adding hydrogen peroxide, penetrant JFC, sodium pyrophosphate and polyester filter cloth into a reactor and stirring, the reactor temperature is 50-60°C, and the temperature is kept for 50-60 minutes to obtain a pretreated polyester filter cloth; S2, adding the pretreated polyester filter cloth and neutral protease into the reactor and stirring, adding sodium hydroxide solution to adjust the pH of the system to 7-8, setting the reactor temperature to 30-40°C, keeping the temperature for reaction for 30-50 minutes, and post-processing to obtain the stripped filter cloth; S3, using a multifunctional finishing agent to perform a two-immersion and two-rolling process on the stripped filter cloth to obtain a dust-removing, water-repellent and oil-repellent filter cloth; S4, cutting and sewing the dust-removing, water-repellent and oil-repellent filter cloth to obtain a dust-removing, water-repellent and oil-repellent filter bag.
2. The method for preparing an industrial dust filter bag resistant to oil stain pollution according to claim 1, characterized in that: In step S1, the hydrogen peroxide, the penetrant JFC, and the sodium pyrophosphate are used in a ratio of 3000-4000 mL: 100-200 g: 300-400 g, and the bath ratio is 100-200 g: 2000-4000 mL.
3. The method for preparing an industrial dust filter bag resistant to oil stain pollution according to claim 1, characterized in that: In step S2, the neutral protease concentration is 5%, the ratio of pre-treated polyester filter cloth and neutral protease usage is 100-200g:2000-3000mL, and the concentration of sodium hydroxide solution is 1%; post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, suction filtration is performed, the filter cake is washed to neutrality and then dried, the filter cake is placed in a drying oven at a temperature of 80-90°C, and dried to constant weight to obtain a stripped filter cloth.
4. The method for preparing an industrial dust filter bag resistant to oil stain pollution according to claim 1, characterized in that: In step S3, the multifunctional finishing agent is obtained by processing the following steps: A1. Add the mixture of compound emulsifier, basic monomer, fluorine-containing monomer, hydrophilic monomer, initiator, crosslinking agent and deionized water into a high shear dispersing emulsifier for dispersion and stirring for 10-20 min and emulsification time for 30-40 min to obtain a pre-emulsion; A2. Add pre-emulsion, compound emulsifier, dispersed zinc oxide powder, initiator and deionized water into the reactor and stir. The temperature of the reactor is raised to 70-80°C, the reaction time is 10-20min, the speed of the reactor is 1000-2000r / min, ammonia water is added to adjust the pH of the system to 6-7, the temperature of the reactor is raised to 85-95°C, the insulation time is 2-3h, the speed of the reactor is 2000-3000r / min, and the multifunctional finishing agent is post-treated.
5. The method for preparing an industrial dust filter bag resistant to oil stain pollution according to claim 4, characterized in that: In step A1, the amount ratio of the composite emulsifier, basic monomer, fluorinated monomer, hydrophilic monomer, initiator, crosslinking agent and deionized water is 200-400g:400-600g:5000-6000g:200-400g:100-200g:100-200g:60000-80000mL, the composite emulsifier is composed of sodium dodecylbenzene sulfonate and alcohol polyoxyethylene ether in a weight ratio of 1:2, the basic monomer is methyl methacrylate, butyl acrylate, acrylic acid The invention discloses a mixture of isooctyl esters, wherein the fluorine-containing monomer is dodecafluoroheptyl methacrylate, the hydrophilic monomer is allyl polyoxyethylene ether, the initiator is ammonium persulfate, and the crosslinking agent is N-hydroxymethyl acrylamide; the rotation speed of the high shear dispersing emulsifier is 5000-6000 r / min; in step A2, the dosage ratio of the pre-emulsion, the compound emulsifier, the dispersed zinc oxide powder, the initiator, and the deionized water is 100-200 g: 100-200 g: 30-60 g: 500-600 g: 8000-9000 mL.
6. The method for preparing an industrial dust filter bag resistant to oil stain pollution according to claim 5, characterized in that: In step A2, the dispersed zinc oxide powder is processed by the following steps: B1. Add nano zinc oxide powder, titanate coupling agent and deionized water into an electromagnetic stirrer, raise the temperature of the stirrer to 90-100°C, keep stirring for 1-2h, and post-treat to obtain modified zinc oxide; B2. Add modified zinc oxide, dispersant and deionized water into an ultrasonic disperser, perform ultrasonic dispersion for 30-40 minutes, and perform post-treatment to obtain dispersed zinc oxide powder.
7. The method for preparing an industrial dust filter bag resistant to oil stain pollution according to claim 6, characterized in that: In step B1, the dosage ratio of the nano zinc oxide powder, titanate coupling agent, and deionized water is: 100-200g: 500-800g: 10000-16000mL, and the speed of the electromagnetic stirrer is 2000-3000r / min; post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, suction filtration is performed, the filter cake is washed to neutrality and then dried, and the filter cake is placed in a drying oven at a temperature of 80-90°C and dried to constant weight to obtain modified zinc oxide; In step B2, the modified zinc oxide, oligomeric sodium acrylate and deionized water are used in a ratio of 100-200 g: 50-100 g: 1000-1500 mL, and the shear speed of the ultrasonic disperser is 4000-5000 r / min; post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, suction filtration is performed, the filter cake is washed to neutrality and then dried, and the filter cake is placed in a drying oven at a temperature of 80-90° C. and dried to constant weight to obtain dispersed zinc oxide powder.
8. The method for preparing an industrial dust filter bag resistant to oil stain pollution according to claim 1, characterized in that: In step S3, the dust-removing, water-repellent and oil-repellent filter cloth is obtained by processing the following steps: C1. Soak the stripped filter cloth and the multifunctional finishing agent in a padding machine tank at a dosage ratio of 100-200g:800-1000mL for 10-20min, squeeze through a two-roll mill, with a rolling pressure of 400-600KN, a rolling speed of 100-150m / min, and a winding speed of 100-280m / min, and pre-bake in a heat setting machine at a pre-bake temperature of 90-110°C, a pre-bake time of 5-10min, a baking temperature of 140-160°C, and a baking time of 5-10min to obtain a pre-impregnated filter cloth; C2. Soak the stripped filter cloth and the multifunctional finishing agent in a dipping mill tank at a dosage ratio of 100-200g:800-1000mL for 20-40min, squeeze through a two-roll mill, with a rolling pressure of 600-800KN, a rolling speed of 150-200m / min, and a winding speed of 200-380m / min, put into a heat setting machine for pre-baking at a pre-baking temperature of 90-110°C for 5-10min, a baking temperature of 170-190°C, and a baking time of 5-10min to obtain a dust-removing, water-repellent and oil-repellent filter cloth.
9. An industrial dust filter bag that is resistant to oil stains, characterized in that: The oil-proof industrial dust filter bag is prepared by the method for preparing an oil-proof industrial dust filter bag as described in any one of claims 1 to 8.